Karl A. Menninger correspondence - Menninger, Karl A. (Karl Augustus), 1893-1990.
TLS (1958 May 20; Topeka, Kans.) from Menninger to Roland H. Berg regarding Berg's upcoming visit to the Menninger Foundation, Topeka, Kans.
Psychiatrist and author. Died 1990.
Collection material in English.
Keywords: Berg, Roland H. -- 1908-; Menninger Foundation; Authors; Psychiatrists